Extensin and Arabinogalactan-Protein Biosynthesis: Glycosyltransferases, Research Challenges, and Biosensors - Showalter, Allan M.; Basu, Debarati (Frontiers in Plant Science, 2016)
Recent research, mostly in Arabidopsis thaliana, has led to the identification and characterization of the glycosyltransferases responsible for the biosynthesis of two of the most functionally important and abundant families of plant cell wall proteins, extensins and arabinogalactan-proteins. Extensin glycosylation involves monogalactosylation of serine residues by O--serine galactosyltransferase and the addition of oligoarabinosides one to five arabinose units in length to contiguous hydroxyproline residues by a set of specific arabinosyltransferase enzymes, which includes hydroxyproline O-β-arabinosyltransferases, β-1,2-arabinosyltransferases, and at least one α-1,3-arabinosyltransferase. AGP glycosylation, however, is much more complex and involves the addition of large arabinogalactan polysaccharide chains to non-contiguous hydroxyproline residues. These arabinogalactan chains are composed of -1,3-galactan backbones decorated with -1,6-galactose side chains that are further modified with -arabinose as well as other sugars, including -(methyl)glucuronic acid, -rhamnose, and -fucose. Specific sets of hydroxyproline O--galactosyltransferases, -1,3-galactosyltransferases, -1,6- galactosyltransferases, -arabinosyltransferases, -glucuronosyltransferases, -rhamnosyltransferases, and -fucosyltransferases are responsible for the synthesis of these complex structures. This mini-review summarizes the EXT and AGP glycosyltransferases identified and characterized to date along with corresponding genetic mutant data, which addresses the functional importance of EXT and AGP glycosylation. In one case, genetic mutant data indicate that the carbohydrate moiety of arabinogalactan-proteins may serve as an extracellular biosensor or signal for normal cellular growth. Finally, future research challenges with respect to understanding the function of these enzymes more completely and discovering and characterizing additional glycosyltransferases responsible for extensin and arabinogalactan-protein biosynthesis are also discussed.